DAMPAK SERVICESCAPE TERHADAP INTENSI KUNJUNG KEMBALI MELALUI KEPUASAN PELANGGAN RESTORAN SELARAS - Septiana, Michelle Dwi Glory; Zaim, Ilma Aulia (Jurnal Pijar, 2023)
In today's business landscape, profit pursuit is closely tied to customer satisfaction. This is especially true in the restaurant industry, where contented customers lead to loyalty, revisits, and enhanced revenue. Selaras Restaurant in Bandung, Indonesia aims to attract Generation Z (ages 13-28) as loyal patrons. Initial interviews with Generation Z patrons revealed that dissatisfaction with the outdated restaurant interior discouraged their return. This gap between Selaras' desired ambiance and Generation Z's preferences, known as Servicescape, impacts revisit intentions. This study employs a quantitative approach using questionnaires to assess Selaras' Gen Z customers. Results show that the physical aspect of Servicescape, like Signs/Symbols/Artifacts, positively influences customer satisfaction and, consequently, revisit intentions. Customer satisfaction also partially mediates the relationship between signs/symbols/artifacts and revisit intentions. These insights should help Selaras Restaurant improve their Servicescape strategy. Future research should consider more factors and samples to better understand restaurant revisit intentions.